PEMANFAATAN TANNIN LIMBAH SERBUK GERGAJI KAYUSEBAGAI ALTERNATIF PEREKAT KAYU ALAMIDENGAN ADITIF POLIURETAN - Annisaa Saraswati S. dan Fifit Astuti (Pelita - Jurnal Penelitian Mahasiswa UNY, 2009)
AbstractThe objective of this research is to ultilize bark waste for tannin‐based adhesive forwood, and polyurethane as additive. It is expected that high tannin content in the bark andpolyurethan additive can support the character of this adhesive.This research followed four steps: 1) finding the problems, 2) identifying the problemsusing the related theory and journal, 3) collecting the data and information, 4) analizing thedata using qualitative data analysis, and 5) finding a conclusion.The result of the research shows that Tannin adhesive has poor adhesive properties,including brittleness, poor wetstrength, and poor wood penetration. This weakness is due toits high reactivity and structural features. To reduce it, the adhesive is modified by addingadditive Poliuretan.Keywords: Bark waste, Tannin adhesive, Polyurethane